The Relationship between Current Ground Stress and Permeability of Coal in Superimposed Zones of Multistage Tectonic Movement. (10th April 2019) - Ni, Xiaoming; Jia, Qifeng; Wang, Yanbin
Abstract : According to the characteristics of the paleostress field and tectonic features at the key moments during tectonic movement after the formation of the no. 3 coal seam, the superimposed areas of different folding zones in the southern section of Shizhuang in central and southern Qinshui Basin were divided. The reservoir permeability of the coal in different superimposed areas was obtained by integrating a laboratory in situ measurement technique, geological strength indices, and multiple parameter fitting of acoustic logging data. The maximum and minimum horizontal principal stresses in different superimposed areas were gained through analysis of the fracturing curve and acoustic logging data. Thus, the relationships between ground stress and permeability in different superimposed areas were revealed. The results show that the relationships between different stresses and permeability were not obvious without considering multistage tectonic superposition. The relationships between the varying stresses and permeability in the same superimposed areas were exponential. The deformation of coal seams in the superimposed areas on the wings of fold belts striking north-central direction was relatively weak, and its permeability was the highest. The permeability in the superimposed areas of the wings of different fold belts in a southeasterly direction was lower than that in the superimposed areas of the wings and the cores of folds. The permeability is the worst in the superimposed areas by the cores and wings of the folds. The results can provide a reference for the study of the heterogeneous deformation of coal reservoirs.